2021
DOI: 10.4103/ijo.ijo_3365_20
|View full text |Cite
|
Sign up to set email alerts
|

Short term changes in corneal stress-strain index and other corneal biomechanical parameters post-laser in situ keratomileusis

Abstract: Purpose: To report the short-term changes in a corneal stress-strain index (SSI) and other corneal biomechanical parameters post-laser in situ keratomileusis (LASIK) surgery. Methods: A retrospective study was conducted at a tertiary eye care center wherein patients who had undergone LASIK (microkeratome blade and femtosecond bladeless LASIK) between July and December 2019 were enrolled. Patients of age group 20–40 years, best-corrected visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Other biomechanical parameters, including HC Deformation Amp., DA ratio, ARTh, IR, SP-A1, and CBI, all underwent significant changes after SMILE ( p < 0.001). This is consistent with the study by ( Kenia et al, 2021 ) that compared the SSI 1 month after laser in situ keratomileuses (LASIK) and femtosecond LASIK and found that its reduction was not statistically significant in either group.…”
Section: Discussionsupporting
confidence: 92%
“…Other biomechanical parameters, including HC Deformation Amp., DA ratio, ARTh, IR, SP-A1, and CBI, all underwent significant changes after SMILE ( p < 0.001). This is consistent with the study by ( Kenia et al, 2021 ) that compared the SSI 1 month after laser in situ keratomileuses (LASIK) and femtosecond LASIK and found that its reduction was not statistically significant in either group.…”
Section: Discussionsupporting
confidence: 92%
“…Ocular surgeries also have an impact on corneal biomechanics. [ 21 22 23 24 25 26 ] Corneal biomechanical parameters in refractive errors such as myopia have been assessed previously;[ 5 6 7 27 28 29 30 31 32 ] however, these reports lack information about corneal SSI. In the present study, we have assessed the corneal biomechanical parameters in myopic eyes, including extreme myopic errors.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] There is only one study now showing SSI changes in early postoperative time following LASIK. [ 7 ] There are more studies needed using the novel SSI and CBI-LVC with longer-term follow ups and also involve the effects of long-term wound healing to check how LASIK differs from SMILE. Differentiating normal corneas postrefractive surgery from post refractive surgery ectasia Though several univariate indices provided by CORVIS ST have been variably successful in differentiating normal corneas from postrefractive surgery ectatic ones in the past, the best index as on date is the CBI-LVC, with sensitivity and specificity over 90% for a cutoff of 0.20.…”
mentioning
confidence: 99%
“…[ 6 ] There is only one study now showing SSI changes in early postoperative time following LASIK. [ 7 ] There are more studies needed using the novel SSI and CBI-LVC with longer-term follow ups and also involve the effects of long-term wound healing to check how LASIK differs from SMILE.…”
mentioning
confidence: 99%